Adherence to long-term therapies : evidence for action (WHO, 2003)
Adherence to therapies is a primary determinant of treatment success. Poor adherence attenuates optimum clinical benefits and therefore reduces the overall effectiveness of health systems. Medicines will not work if you do not take them. Medicines will not be effective if patients do not follow prescribed treatment - yet in developed countries only 50% of patients who suffer from chronic diseases adhere to treatment recommendations. In developing countries, when taken together with poor access to health care, lack of appropriate diagnosis, and limited access to medicines, poor adherence is threatening to render futile any effort to tackle chronic conditions such as diabetes, depression and HIV/AIDS. This report is based on an exhaustive review of the published literature on the definitions, measurements, epidemiology, economics, and interventions applied to nine chronic conditions and their risk factors. These are: asthma, cancer (palliative care), depression, diabetes, epilepsy, HIV/AIDS, hypertension, tobacco smoking, and tuberculosis. Intended for clinical practitioners, health managers and policy-makers, this report provides a concise summary of the consequences of poor adherence for health and economics. It also discusses the options available for improving adherence, and demonstrates the potential impact on desired health outcomes and health care budgets. It is hoped that this report will lead to new thinking on policy development, and action on adherence to long-term therapies.
Keywords: adherence pacienta; Chronic Disease; Drug Therapy; terapie; veřejné zdravotnictví; farmakoterapie; lékařství; dlouhodobá péče; Long-Term Care; LÉKAŘSTVÍ ZALOŽENÉ NA FAKTECH; Patient Compliance; chronická nemoc